Testing for a Time-Varying Price-Cost Markup in the Euro Area Inflation Process - Christopher Bowdler; Eilev S. Jansen (Norges Bank, 2004)
Empirical models of inflation often incorporate equilibrium correction effects based upon levels of prices and input costs. Such models assume that the steady-state price-cost markup is constant, but recent research suggests that this may not be true for the Euro area economy, which has undergone major structural reforms over the last 25 years. We allow for permanent shifts in the markup factor through estimating an inflation equation that includes a time-varying intercept. The model suggests that a reduction in the markup contributed to disinflation in the Euro area during the period 1981-2000.
hdl:11250/2498544; Additional information: This is a revised version of ECB Working Paper 306 (Bowdler and Jansen (2004)), which was written while the second author was a Research Visitor to DG Research, European Central Bank, Frankfurt, from February through June 2003. The work benefitted greatly from a one week visit from the first author to the same institution in May 2003. The first author acknowledges financial support from a British Academy post-doctoral fellowship. The revision has been carried out while the second author was visiting Department of Economics, University of California San Diego. The hospitality and excellent working conditions offered there are gratefully acknowledged. We are also grateful for the constructive criticism provided by an anonymous ECB referee, and for comments from James Hamilton, Heino Bohn Nielsen and seminar participants at Norges Bank, University of California San Diego and Brunel University. The views expressed in this paper represent exclusively the views of the authors and do not necessarily reflect those of the European Central Bank or Norges Bank.
Keywords: C22; C32; E31; 330; inflation; price-cost markup; cointegration; time-varying intercept; dynamic modelling